An efficient vector Preisach hysteresis model based on a novel rotational operator - Sutor, Alexander; Kallwies, Jan; Lerch, Reinhard (Journal of Applied Physics, 2012)
The vectorial modeling of hysteresis phenomena is an important task with respect to precise numerical simulation of ferromagnetic materials. Many vector models are based on extended Preisach models. Approaches are known where the scalar Preisach models are defined in different space directions and the results are calculated by summation or integration. Within this approach, we suggest a Preisach model that uses only one Preisach plane, but an additional rotational plane. This rotational plane practically defines a direction for each Preisach element. Therefore, this operator can be evaluated in a very efficient way. (C) 2012 American Institute of Physics. [doi: 10.1063/1.3672069]

Magnetische Vektorhysterese: Messtechnik und Modellierung - Sutor, Alexander; Kallwies, Jan; Lerch, Reinhard (XV. Messtechnisches Symposium, 2011)

Vectorial Measuring and Modelling of Magnetic Hysteresis - Sutor, Alexander; Kallwies, Jan; Lerch, Reinhard (Technisches Messen, 2012)
The quality of numerical simulations decisively depends on the used material models and their parameters. Only with good model descriptions, the behavior of components such as sensors and actuators can reliably be computed ahead. If magnetic materials are highly driven, which is necessary for an efficient use of an actuator material, hysteresis phenomena can no longer be ignored. Therefore, models are needed which can map this hysteresis phenomena, as well as correct values for the model parameters. Therefore, measurement techniques are necessary for the reliable determination of these model parameters. This paper discusses a measurement setup for magnetic vector hysteresis, the vector vibrating sample magnetometer (VVSM). The measurement setup is compared with other measurement methods. Furthermore, the parameters for a new vectorial hysteresis model are determined. The new model proposed by us is based on the classic Preisach model of hysteresis. This scalar model is extended by a rotation operator which maps a direction to each Preisach weight. The model is tested by comparing its performance to the VVSM measurements for different materials.
Keywords: Magnetometer; magnetization vector; vectorial measurement; hysteresis